The effect of tightening again on bolt loosening under transverse load: Experimental and finite element analysis. (October 2022) - Liu, Zhifeng; Yan, Xing; Zheng, Mingpo; Wang, Yuezhen; Chen, Wentao; Li, Ying
Abstract: Bolt loosening is one of the most common failure modes in bolted joints. Tightening again is often used to compensate for the loss of clamping force in many critical applications. In this study, the effect of load control modes and lubrication conditions on bolt loosening were studied by experiments. Then, a series of experiments were carried out on the tightening again after bolt loosening under transverse load. Finally, in order to study the cause of fatigue fracture, FEA was carried out by using an accurate three-dimensional finite element model. The results show that the bolt loosening is mainly caused by relative motion between the two clamped plates. With oil lubrication, the bolt clamping force was able to reach the magnitude comparable to the initial preload when the nut is released to a specific angle (30° ∼ 60°) before tightening again. Nevertheless, the times of tightening again should be limited to avoid fatigue fracture of the bolt.